Insight Into the Mechanisms and the Challenges on Stem Cell-Based Therapies for Cerebral Ischemic Stroke - Liu, Huiyong; Reiter, Sydney; Zhou, Xiangyue; Chen, Hanmin; Ou, Yibo; Lenahan, Cameron; He, Yue (Frontiers in Cellular Neuroscience, 2021)
Stroke is the most common type of cerebrovascular disease, and remains a major cause of death and disability worldwide. Cerebral ischemic stroke is caused by a reduction in blood flow to the brain. In this disease, two major zones of injury are identified: the lesion core, in which cells rapidly progress toward death; and the ischemic penumbra (surrounding the lesion core), which defined as hypoperfusion tissue but may still viable and can be repaired. Only two methods are approved by the Food and Drug Administration (FDA) include intravenous thrombolytic therapy and the endovascular thrombectomy, but the narrow therapeutic window is the limitation and a low percentage of stroke patients actually receive these treatments. Developments in stem cell therapy have introduced renewed hope to patients with ischemic stroke due to its potential effect for reversing the neurological sequelae. Over the last few decades, in animal tests and some clinical trials ischemic stroke has been experimentally treated with many types of stem cells. However, several technical and ethical challenges must be overcome before stem cells could be a choice for the treatment of stroke in clinical. In this review, we summarize the mechanisms, the process, and the challenges of using stem cell in stroke treatment, as well as the new trends.